Evaluation of optimised flight trajectories for conventional and novel aircraft and engine integrated systems - Gu, Weiqun (Cranfield University, 2013)
Today, the air transport industry has become an essential element of global society by its great contributions to the wide exchanges of cultures/people and to the rapid growth in the world economy. However, on the other hand, the adverse impacts on the environment caused by air transport, such as air pollution, noise and climate change, are drawing, increasingly, growing public concern. In order to address the steady growth in air-travel demand in the next decades through an environmentally-friendly way and realise the ACARE 2020 environmental goals, The Clean Sky programme has been launched by European Union over the period 2008 – 2013. The project research, described in this thesis and sponsored by the Clean Sky programme, aims at evaluating the feasibility of reducing the environmental impact of commercial aviation through the introduction of changes in the aircraft operational rules and procedures, as well as the application of the new-generation propfan (open rotor) engine, based on flight trajectory multidisciplinary optimisation and analysis of commercial aircraft. In order to accomplish the above research objectives, a complete methodology to achieve and realise optimum flight trajectories has been initially proposed. Then, 12 component-level models which function as simulating different disciplines, such as aircraft performance, engine performance, engine gaseous emission, and flight noise, have been developed or selected/adopted. Further, nine system-level integration and optimisation models were built. These system-level models simulate flights from Amsterdam Schiphol airport in the Netherlands to Munich airport in Germany flown by different types of aircraft through different flight phases with different optimisation objectives. Finally, detailed investigations into the flight trajectory optimisations were performed, extensive optimisation results were achieved and corresponding description, analysis and comparisons were provided. The main contributions of this work to knowledge broadly comprise the following: 1) the further development regarding the methodology of flight trajectory multidisciplinary optimisation; 2) previous work on aircraft trajectory optimisation has often considered fixed objectives over the complete flight trajectory. This research focused on representative flight phases of a flight mission with different optimisation objectives, namely, noise impact and fuel burn during the departure phase; fuel burn and flight time during en route phase; and noise impact and NOx emission during the arrival phase; 3) this research has extended the current flight trajectory optimisations to turboprop and propfan equipped aircraft. As a result, a relative complete 2D flight trajectory multidisciplinary optimisation spectrum, spanned by primary commercial aircraft types, primary flight phases and primary optimisation objectives of interest, has been built. Although encouraging progress have been achieved, this project research, as with any other research activity, is also only ‘on the way’ rather than coming to the ‘end’ point. There are still many aspects which can be improved further and there is still much new research and exploration which can be investigated further. All these have also been suggested in this thesis.
Keywords: flight trajectory; multidisciplinary; integration; optimisation; modelling; performance; gaseous emissions; flight noise